2011
DOI: 10.1007/s11689-011-9098-z
|View full text |Cite
|
Sign up to set email alerts
|

Language development after cochlear implantation: an epigenetic model

Abstract: Growing evidence supports the notion that dynamic gene expression, subject to epigenetic control, organizes multiple influences to enable a child to learn to listen and to talk. Here, we review neurobiological and genetic influences on spoken language development in the context of results of a longitudinal trial of cochlear implantation of young children with severe to profound sensorineural hearing loss in the Childhood Development after Cochlear Implantation study. We specifically examine the results of coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 122 publications
(144 reference statements)
1
46
0
8
Order By: Relevance
“…visual) systems (Fagan & Pisoni, 2010;Ruben, 1997;Sharma et al, 2009). Delayed access to adequate hearing not only leads to setbacks in language acquisition, but can also impact long-term academic performance, social interaction (Polat, 2003), employment, and quality of life (Markman et al, 2011). To circumvent such enduring implications of significant hearing loss, the Joint Committee of Infant Hearing aims for detection of hearing loss by one month, confirmation by three months, and intervention by six months of age; known as the 1-3-6 guidelines (JCIH, 2007;Muse et al, 2013).…”
mentioning
confidence: 99%
“…visual) systems (Fagan & Pisoni, 2010;Ruben, 1997;Sharma et al, 2009). Delayed access to adequate hearing not only leads to setbacks in language acquisition, but can also impact long-term academic performance, social interaction (Polat, 2003), employment, and quality of life (Markman et al, 2011). To circumvent such enduring implications of significant hearing loss, the Joint Committee of Infant Hearing aims for detection of hearing loss by one month, confirmation by three months, and intervention by six months of age; known as the 1-3-6 guidelines (JCIH, 2007;Muse et al, 2013).…”
mentioning
confidence: 99%
“…Models of early language learning have long emphasized the key role played by early caregiver interactions in facilitating communicative intent and attentional frames, setting the stage for imitative learning of linguistic expression. 8-13 Observational studies have shown that hearing mothers of young deaf children engage in more controlling, directive, and intrusive interactions with their children and display less positive affect compared with mothers of hearing children. 14-16 The consequences of these dyadic interactions include less secure attachment, difficulty sustaining attention, and slower development of communicative competence.…”
mentioning
confidence: 99%
“…Ao lançar mão de recursos empíricos aliados a uma análise do referencial teórico utilizado para este estudo permitiu-se ponderar sobre a qualidade da comunicação e, com isso, notar a relação entre estes dois fatores, a ponto de a linguagem influenciar a qualidade da aprendizagem, o que impõe a necessidade de se conhecer de forma mais aprofundada os conceitos e mecanismos inerentes à linguagem e sua relação com a aprendizagem, e isso pode ser sustentado na afirmação de (MARKMAN et al, 2011) de que a "A linguagem fornece as ferramentas para nos revelar aos outros no estabelecimento e manutenção de relacionamentos e impulsiona o aprendizado perceptual que contribui para a cognição." Vemos, então que a linguagem, além de ser uma forma de expressar a si mesmo, também é uma poderosa ferramenta de construção da subjetividade do indivíduo, possibilitando que este crie uma estrutura acessível de seus conhecimentos.…”
Section: Linguagem E Aprendizagemunclassified